Effects of oral isotretinoin therapy on the nasal cavities, - Tasli,Hamdi (2020)
Abstract Introduction Isotretinoin (13 cis-retinoic acid) is the most effective treatment for acne vulgaris and is the only treatment option that can provide either remission or a permanent cure. Objective The aim of this study was to use both subjective and objective methods to assess the nasal complaints of patients with severe acne who received oral isotretinoin therapy. Methods Fifty-four subjects were enrolled in the study. All the subjects were assessed with subjective (NOSE and VAS questionnaires) and objective (rhinomanometry and saccharine) tests to determine the severity of their nasal complaints. Results The mean severity scores (min: 0; max: 100) for nasal dryness/crusting and epistaxis were 0.47 ± 1.48 (0-5); 0.35 ± 1.30 (0-5) at admission, 3.57 ± 4.45 (0-10); 2.26 ± 4.71 (0-20) at the first month, and 4.28 ± 6 (0-20); 2.26 ± 4.71 (0-20) at the third month of the treatment respectively. Total nasal resistance of 0.195 ± 0.079 (0.12-0.56) Pa/cm3/s at admission, 0.21 ± 0.084 (0.12-0.54) Pa/cm3/s at the first month, and 0.216 ± 0.081 (0.14-0.54) Pa/cm3/s at the third month. Conclusion Oral isotretinoin therapy can cause the complaint of nasal obstruction. In addition, nasal complaints, such as dryness/crusting and epistaxis, significantly increase in patients during the therapy schedule.